Influence of the sFlt-1/PlGF Ratio on Clinical Decision-Making in Women with Suspected Preeclampsia - Klein, Evelyn; Schlembach, Dietmar; Ramoni, Angela; Langer, Elena; Bahlmann, Franz; Grill, Sabine; Schaffenrath, Helene; van der Does, Reinhard; Messinger, Diethelm; Verhagen-Kamerbeek, Wilma D. J.; Reim, Manfred; Hund, Martin; et al. (PLOS ONE, 2016)
Objective To evaluate the influence of the soluble fms-like tyrosine kinase 1/placental growth factor ratio in physicians’ decision making in pregnant women with signs and symptoms of preeclampsia in routine clinical practice. Methods A multicenter, prospective, open, non-interventional study enrolled pregnant women presenting with preeclampsia signs and symptoms in several European perinatal care centers. Before the soluble fms-like tyrosine kinase 1/placental growth factor ratio result was known, physicians documented intended clinical procedures using an iPad® application (data locked/time stamped). After the result was available, clinical decisions were confirmed or revised and documented. An independent adjudication committee evaluated the appropriateness of decisions based on maternal/fetal outcomes. Clinician decision making with regard to hospitalization was the primary outcome. Results In 16.9% of mothers (20/118) the hospitalization decision was changed after knowledge of the ratio. In 13 women (11.0%), the initial decision to hospitalize was changed to no hospitalization. In seven women (5.9%) the revised decision was hospitalization. All revised decisions were considered appropriate by the panel of adjudicators (McNemar test; p < 0.0001). Conclusions The use of the soluble fms-like tyrosine kinase 1/placental growth factor test influenced clinical decision making towards appropriate hospitalization in a considerable proportion of women with suspected preeclampsia. This is the first study to demonstrate the impact of angiogenic biomarkers on decision making in a routine clinical practice.